Clinical Characteristics and Spermatogenesis in Patients with Congenital Hypogonadotropic Hypogonadism Caused by FGFR1 Mutations - Shuying Li; Yaling Zhao; Min Nie; Wanlu Ma; Xi Wang; Wen Ji; Yufan Yang; Ming Hao; Bingqing Yu; Yinjie Gao; Jiangfeng Mao; Xueyan Wu (International Journal of Endocrinology)
Objective. The aim of this study was to investigate the clinical characteristics of patients diagnosed with congenital hypogonadotropic hypogonadism (CHH) caused by FGFR1 (fibroblast growth factor receptor 1) gene mutations and to evaluate the effect of gonadotropin or pulsatile gonadotropin-releasing hormone (GnRH) therapy on spermatogenesis. Methods. A retrospective study was conducted on CHH patients admitted to Peking Union Medical College Hospital from January 2012 to March 2020. Clinical features and laboratory results were recorded. Testicular volume and sperm count responding to gonadotropin and pulsatile GnRH therapy were compared between the FGFR1 mutation group and the mutation-negative group. Results. (1) FGFR1 mutation group included 14 patients who received sperm-induction therapy, and the mutation-negative group enrolled 25 CHH patients. (2) The incidence of cryptorchidism was 50.0% (7/14) and 12.0% (3/25) in the FGFR1 group and the mutation-negative group, respectively (p=0.019). The baseline testicular volume of the FGFR1 mutation group was smaller than that of the mutation-negative group, 1.6 (0.5–2.0) mL vs. 2 (1.75–4) mL (p=0.033). The baseline luteinizing hormone (LH), Follicle-stimulating hormone (FSH), and testosterone levels were similar between the two groups. (3) Using the Kaplan–Meier and log-rank tests for the analysis of spermatogenesis, it was found that there was no significant difference in the first sperm appearance between the FGFR1 mutation group and the mutation-negative group (χ2 = 1.974, p=0.160). The median time of spermatogenesis in the FGFR1 mutation group was longer than that in the mutation-negative group, 16 months vs. 10 months, respectively. The cumulative spermatogenesis success rate at 12 months in the FGFR1 mutation group (35.71%) was lower than that in the mutation-negative group (68.75%) (p=0.047). The sperm concentration in the mutation-negative group was more easily achieved for different thresholds compared with that in the FGFR1 mutation group, but no significant difference was observed (p>0.05) between the two groups. The last follow-up examination showed that the testicular volume was 7.00 (4.75–12.00) mL and 10.56 ± 4.82 mL (p=0.098), the ejaculate volume of sperm was 2.20 (1.40–2.26) mL and 3.06 ± 1.42 mL (p=0.175), and the sperm concentration was 7.19 (1.00–9.91) million/mL and 18.80 (4.58–53.62) million/mL (p=0.038) in the FGFR1 mutation and mutation-negative groups, respectively, while the sperm motility (A%, A + B%, and A + B + C%) was similar for the two groups (p=0.839, 0.909, and 0.759, respectively). The testosterone level during treatment was 366.02 ± 167.03 ng/dL and 362.27 ± 212.86 ng/dL in the FGFR1 mutation and mutation-negative groups, respectively (p=0.956). Conclusion. Patients with FGFR1 mutations have a higher prevalence of cryptorchidism and smaller testicular volume. Although patients with FGFR1 mutations have a similar rate of success for spermatogenesis compared to that of the mutation-negative patients, a longer treatment period was required and a lower sperm concentration was achieved.